Peran Supervisi Pembelajaran Dalam Meningkatkan Kinerja Guru Di Madrasah Aliyah Al-Istiqomah Kota Sukabumi - M. Alwi AF; Rizki Kurniawan; Siti Qomariyah (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Learning supervision is all the efforts of educational leaders to assist, supervise, improve, develop teachers in their learning process, so that what they do can be carried out effectively and efficiently in achieving educational goals. The focus of this research is how is the implementation of academic supervision in improving teacher performance, how are academic supervision techniques in improving teacher performance, what are the obstacles to academic supervision in improving teacher performance. The purpose of this research is to find out the role of learning supervision in improving teacher performance in Madrasah Aliyah Al-istiqomah. field research research (field). Data collection techniques using structured interviews, passive participatory observation, and documentation. Data analysis uses data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study uses source triangulation. As a result, this learning supervision is needed. Due to being a medium for madrasah/school heads in order to supervise and foster the performance of Madrasah Aliyah Al-istiqoamh teachers, especially in the field of the learning process, it is hoped that the implementation of this learning supervision will bring significant changes.